2014
DOI: 10.1016/j.jjcc.2013.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Aortic stiffness is increased in patients with premature coronary artery disease: A tissue Doppler imaging study

Abstract: Arterial stiffness is increased in patients with premature CAD. EAo of the anterior wall of ascending aorta measured with pulse-wave TDI echocardiography is correlated with arterial stiffening and is decreased in patients with premature CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…In [63], it is reported that arterial stiffness is increased in patients with premature coronary disease. However, the patient's diagnostic cardiac catheterization revealed no signs of significant coronary obstruction.…”
Section: A Patient Description and Data Acquisitionmentioning
confidence: 99%
“…In [63], it is reported that arterial stiffness is increased in patients with premature coronary disease. However, the patient's diagnostic cardiac catheterization revealed no signs of significant coronary obstruction.…”
Section: A Patient Description and Data Acquisitionmentioning
confidence: 99%
“…However, the mechanisms underlying the minimal elevations of the serum TnT are not yet fully understood. On the other hand, increased arterial stiffness/abnormal central hemodynamics have been much focused on as independent risk factors for cardiovascular events [7][8][9][10]. Bai et al reported the existence of a correlation between increased arterial stiffness, as reflected by the carotid-femoral pulse wave velocity, and minimal elevations of the serum cTnT levels in elderly Chinese subjects [11].…”
Section: Introductionmentioning
confidence: 99%
“…Güngör et al demonstrated that the early diastolic velocity of the anterior wall of the ascending aorta measured with pulse‐wave tissue Doppler imaging echocardiography correlates with arterial stiffening and is decreased in patients with premature CAD 36. However, the tissue Doppler imaging technique is angle dependent and is influenced by tethering or translational motion 15.…”
Section: Discussionmentioning
confidence: 99%